The Effect of Health and Economic Sector Government Expenditure on Human Development Index - Nainggolan, Raja Mangaratua (Universitas Gorontalo, 2024)
Human development is a major factor in increasing welfare and economic growth. This study aims to analyze how much influence government spending on the health and economic sectors has on the District / City Human Development Index in Papua Province 2011-2018. This study uses secondary data sourced from the Badan Pusat Statistik and the Direktorat Jendral Perimbangan Keuangan. The method of analysis used in this research is panel data regression with the Random Effect Model (REM) selected method. The results of this study indicate that government spending in the health and economic sectors has a positive and significant effect both partially and collectively on the Human Development Index in Papua Province.